The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.34257/gjmbrevol21is1pg19
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Marketing towards the Purchase Intention among Generation Y and Z with Reference to Franchise Fast Food Industry in Colombo District

Abstract: Out of the source characteristics, the study discovers the impact of social media marketing towards purchase intention among generation Y and Z referring to fast food franchises in the Colombo district. Although there were many studies conducted in other countries on the impact of social media marketing towards purchase intention, there is a deficiency of literature in the Sri Lankan context regarding the same area. Furthermore, this study explores how the purchase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…In accordance with previously published results, the current study also reports that, "friends' likes" had the third most influential factor on generation Z consumers' fast food purchase intention. Samarasinghe (2021) reported that the social media factor "comments" had a positive impact on customers' purchase intention (t=3.483, p<0.05). Furthermore, Appel et al (2020) concluded that "comments" had a positive impact on customers' purchase intention, and the current study emphasizes the least impact of "comments" on generation Z consumers in fast food purchase intention compared to other variables in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previously published results, the current study also reports that, "friends' likes" had the third most influential factor on generation Z consumers' fast food purchase intention. Samarasinghe (2021) reported that the social media factor "comments" had a positive impact on customers' purchase intention (t=3.483, p<0.05). Furthermore, Appel et al (2020) concluded that "comments" had a positive impact on customers' purchase intention, and the current study emphasizes the least impact of "comments" on generation Z consumers in fast food purchase intention compared to other variables in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previously published results, the current study also reports that, "friends' likes" had the third most influential factor on generation Z consumers' fast food purchase intention. Samarasinghe (2021) reported that the social media factor "comments" had a positive impact on customers' purchase intention (t=3.483, p<0.05). Furthermore, Appel et al (2020) concluded that "comments" had a positive impact on customers' purchase intention, and the current study emphasizes the least impact of "comments" on generation Z consumers in fast food purchase intention compared to other variables in this study.…”
Section: Discussionmentioning
confidence: 99%